TINJAUAN YURIDIS TERHADAP KEDUDUKAN BADAN PELAKSANA KEGIATAN USAHA HULU MINYAK DAN GAS BUMI PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 36/PUU-X/2012 - daris a raft ginting; gusliana H.B.; dodi haryono (Universitas Lampung, 2014)
Relations between the Implementing Agencies of Oil and Gas with Business Entities or Permanent Establishment has put the State and Business Entities or Permanent Establishments that manage oil and gas are in the same position. As a result, the State lost the discretion to make regulations for the benefit of the People. While the Government in carrying out the functions of state control over oil and natural gas resources should has the discretion to make regulation that is profitable for the prosperity of the entire community. Those conditions are so far from optimality. Indonesian oil and gas industry is still heavily dependent on foreign domination. Do Indonesian people ask for judicial review of Oil and Gas Law to the Constitutional Court. While the result of Constitutional Court is the Implementing Agencies of Oil and Gas disbanded. As a replacement, the Government through Presidential Decree No. 9 of 2013 on Maintenance of Management for Upstream Oil and Gas takes over all the functions and duties of the Implementing Agencies of Oil and Gas. Keywords: Oil and Gas, Implementing Agencies of Oil and Gas, functions of state control